Intermittent Fasting and GERD Symptoms: A Cross-Sectional Study in a Medical Faculty Academic Community - Cherry Permata Putri; Ismatul Fauziah Rambe (Asosiasi Dosen Muda Indonesia, 2026)
Gastroesophageal Reflux Disease (GERD) is a chronic gastrointestinal disorder caused by the backflow of gastric contents into the esophagus and may reduce quality of life. Intermittent fasting (IF) is increasingly practiced among productive-age groups, including academic communities, yet alterations in eating windows may influence gastric acid dynamics and gastrointestinal motility, making its relationship with GERD symptoms clinically relevant. Objective: This study aimed to examine the association between intermittent fasting habits and the occurrence of GERD symptoms among the academic community at the Faculty of Medicine and Health Sciences, Universitas Muhammadiyah Sumatera Utara. Methodology: An analytic observational study with a cross-sectional design was conducted among 64 respondents selected using purposive sampling. Data were collected using a structured questionnaire and analyzed with SPSS. The association between IF habits and GERD symptoms was tested using the Chi-square test at a significance level of p < 0.05. Findings: The analysis showed no statistically significant association between intermittent fasting habits and GERD symptoms (p = 0.633). Research implications: These findings suggest that intermittent fasting, as practiced in this population, may not be a key determinant of GERD symptoms; therefore, prevention and counseling efforts should emphasize other modifiable factors (e.g., meal composition, late-night eating, stress, caffeine intake, or obesity-related risk) when managing reflux complaints in academic settings. Originality/value: This study provides context-specific evidence on the IF–GERD symptom relationship within an Indonesian medical faculty academic community using a standardized symptom assessment approach, contributing local data to an area where findings remain variable across populations.